Asset Values, Interest-Rate Changes, and Duration - Cooper, I. A. (Journal of Financial and Quantitative Analysis, 1977)
Much effort has been recently devoted to investigating and expounding the properties of the measure called “duration.” Two properties claimed for duration are (1) that it is a good indicator of the average life of a payments stream and (2) that it measures the elasticity of the present value of such a stream with respect to the discount rate. Unfortunately the theoretical justifications of the second, more important, property have been based upon the analysis of either a change in a discount rate constant for all future time periods, or, more generally, a parallel shift in the term structure of interest rates.